2016
DOI: 10.1111/efp.12308
|View full text |Cite
|
Sign up to set email alerts
|

First record ofNeocatenulostroma germanicumon pines in Lithuania and Ukraine and its co‐occurrence withDothistromaspp. and other pathogens

Abstract: Neocatenulostroma germanicum (syn. Catenulostroma germanicum), an ascomycetous fungus, is recorded for the first time in Lithuania and the Ukraine. N. germanicum was observed colonizing pine needles and causing needle blight symptoms on Pinus mugo in coastal areas of Lithuania, Pinus nigra subsp. pallasiania in southern areas of the Ukraine and Pinus sylvestris in both coastal and continental areas of Lithuania. N. ger manicum was commonly associated with Dothistroma spp. and/or Lecanosticta acicola on needles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
2
19
1
Order By: Relevance
“…However, it can occur alone, and in such situations, it produces blight symptoms very similar to those induced by Dothistroma spp. Markovskaja et al (2016) found N. germanicum co-occurring with C. minus and with species of Alternaria, Cladosporium, Diplodia, Lophodermium and Pestalotiopsis, which were detected in the present study and are considered as possible opportunistic pathogens. The temperatures, radiation and cold, hot, dry or salty environments (Gorbushina et al, 2003).…”
Section: Less Common Fungal Pathogens In Needles Of 9-year-old Scotsupporting
confidence: 59%
See 4 more Smart Citations
“…However, it can occur alone, and in such situations, it produces blight symptoms very similar to those induced by Dothistroma spp. Markovskaja et al (2016) found N. germanicum co-occurring with C. minus and with species of Alternaria, Cladosporium, Diplodia, Lophodermium and Pestalotiopsis, which were detected in the present study and are considered as possible opportunistic pathogens. The temperatures, radiation and cold, hot, dry or salty environments (Gorbushina et al, 2003).…”
Section: Less Common Fungal Pathogens In Needles Of 9-year-old Scotsupporting
confidence: 59%
“…pallasiania in southern areas of Ukraine (Markovskaja, Kačergius, Davydenko, & Fraser, 2016). It had previously been found in needles of P. mugo and P. sylvestris in coastal and continental areas of Lithuania and of P. nigra subsp.…”
Section: Less Common Fungal Pathogens In Needles Of 9-year-old Scotmentioning
confidence: 67%
See 3 more Smart Citations